HUBUNGAN SELF CONCEPT DENGAN PENYESUAIAN STADIUM PSIKOLOGIS PASIEN KANKER PADA PENDERITA KANKER PAYUDARA STADIUM LANJUT DI RUMAH SAKIT HASAN SADIKIN BANDUNG PRESPEKTIF PSIKOLOGI ISLAM - Mardenny, Mardenny (Islamijah: Journal of Islamic Social Sciences, 2023)
The purpose of the study was to empirically determine the relationship between self-concept and psychological adjustment stage of cancer patients. The method used was correlational; and the study conducted was population study,  because the number of patients with advanced breast cancer who regularly carry out checks at Hasan Sadikin hospital that met the criteria was only about 20 people. The hypothesis of the proposed research was:  the more positive the self concept of the patients with advanced breast cancer, the faster the patients will reach the stage of acceptance in undergoing psychological stages. The main variable in this study is the Self Concept. The data were obtained by using the Tennessee Self Concept Scale of Fitts.  The second variable is the psychological adjustment stage of the cancer patients. The data were obtained by using a scale that was made using the Likert scale.  Data measuring was in the form of ordinal data and data processing  was carried out by using Spearman rank coefficient test (rs). From the data processing with a significance level α = 0.05, thit (8,435) > ttab (1,734) was obtained. This means that H0 is rejected and H1 is accepted, thus it can be concluded that there is a significant relationship between self-concept and psychological adjustment stage of cancer patients. This means that the more positive self concept of patients with advanced breast cancer, the faster the patient will be in undergoing psychological stages until it reaches the stage of acceptance.